Changes in the aroma of organic passion fruit (Passiflora edulis Sims f. flavicarpa Deg.) during ripeness - Janzantti, Natalia S. [UNESP]; Monteiro, Magali [UNESP] (Elsevier B.V., 2014)
The odoriferous importance of volatile compounds during maturation of organic passion fruit was studied. The volatile compounds were analyzed using GC-FID-OSME and GC-MS. The volatile profile changed throughout maturation. Relative peak area improved from the 1/3 to 2/3 yellow skin color state of ripeness and was still improved from the 2/3 to 3/3, but the profile remained. Ethyl butanoate showed the highest relative peak area and importance for the aroma of the organic passion fruit in the 1/3 yellow skin color. Ethyl butanoate and hexanoate, propyl acetate and alpha-terpineol showed odoriferous importance from the 2/3 yellow skin color, and together with diethyl carbonate and cis-3-hexen-1-ol were the most important compounds in the 3/3 yellow skin color state of ripeness. PCA allowed clearly differentiate all ripening states, indicating that hexanal and caramel, earthy and synthetic aroma were most closely associated with the unripe passion fruit. 2-methylpropyl acetate characterized the passion fruit at the 2/3 yellow skin color together with cis-beta-ocimene, benzaldehyde and aroma sweet and passion fruit, skin, which also were associated with the 3/3 yellow skin color. Esters, terpenes, alcohols, octanal, dodecanol and aroma of passion fruit, fruity, citric, candy and plastic were closely associated with the whole maturation. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Passion fruit; Aroma; Olfactometry; State of ripeness; Organic cultivation